New approach for fast identification of cyclitols by MALDI‐TOF mass spectrometry. Issue 5 (6th May 2018) - Al‐Suod, Hossam; Pomastowski, Paweł; Ligor, Magdalena; Railean‐Plugaru, Viorica; Buszewski, Bogusław
Abstract: Introduction: Alfalfa ( Medicago sativa L.) is the subject of many studies due to its numerous chemical constituents and beneficial properties. Among these constituents are cyclitols, which have attracted attention due to the variety of biological properties they have. Objective: A rapid and sensitive analytical procedure based on matrix‐assisted laser desorption ionisation technique with time‐of‐flight and mass spectrometry (MALDI‐TOF‐MS) analysis was used for the first time for the identification of three cyclitols from different parts of alfalfa. Methodology: Plant extracts were prepared and purified using Soxhlet extraction and solid‐phase extraction (SPE). Then, samples were dissolved in α‐cyano‐4‐hydroxycinnamic acid (HCCA) matrix, and subjected to MALDI‐TOF‐MS analysis. Results: The ion at m / z 524.0 was distributed in all standards and in leaves and stem extracts. In turn, the signal at m / z 335.1 was found in all standards and all alfalfa extracts. The ion at m / z 144.1 was found just ford ‐ chiro ‐inositol and distributed in all extracts. Both signals at m / z 265.9 and 250.0 were found only inl ‐ chiro ‐inositol standard and the extract of stem. However, the ion at m / z 177.1 was found ind ‐pinitol standard and the extract of leaves. Based on molecular weights, information on fragment ions obtained by MALDI‐TOF‐MS, and the chemistry of cyclitols, we successfully identified three cyclitols (d ‐ chiro ‐inositol, l ‐ chiro ‐inositol, d ‐pinitol) in different parts of alfalfa (leaves, stem, flowers). Conclusion: The obtained results in this study proved that MALDI‐TOF‐MS is a rapid, sensitive and very powerful tool for identification of cyclitols within plants and has the potential to differentiate between enantiomers. Abstract : A new analytical procedure based on matrix‐assisted laser desorption ionization technique (MALDI) with time‐of‐flight (TOF) and mass spectrometer analyzer was used for the first time for the identification of three cyclitols from different parts of alfalfa. The obtained results proved that MALDI‐TOF‐MS is a rapid, sensitive and powerful tool, which can be used for identification of cyclitols in plant materials. Moreover, the technique has the potential to differentiate between cyclitols enantiomers.